2013
DOI: 10.1016/j.molonc.2013.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Collective migration of cancer‐associated fibroblasts is enhanced by overexpression of tight junction‐associated proteins claudin‐11 and occludin

Abstract: It has been suggested that cancer-associated fibroblasts (CAFs) positioned at the desmoplastic areas of various types of cancer are capable of executing a migratory program, characterized by accelerated motility and collective configuration. Since CAFs are reprogrammed derivatives of normal progenitors, including quiescent fibroblasts, we hypothesized that such migratory program could be context-dependent, thus being regulated by specific paracrine signals from the adjacent cancer population. Using the traditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
35
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 67 publications
1
35
2
Order By: Relevance
“…The OCLN, ZO-1, CLDN1, CLDN3, and CLDN4 are the main tight-junction proteins in the mammary gland. [25][26][27] In the current study, mammary expression of these proteins, except OCLN, showed no difference in the cows fed two diets. Occludin plays an important role in forming the tight junction paracellular permeability barrier.…”
Section: Resultscontrasting
confidence: 41%
See 3 more Smart Citations
“…The OCLN, ZO-1, CLDN1, CLDN3, and CLDN4 are the main tight-junction proteins in the mammary gland. [25][26][27] In the current study, mammary expression of these proteins, except OCLN, showed no difference in the cows fed two diets. Occludin plays an important role in forming the tight junction paracellular permeability barrier.…”
Section: Resultscontrasting
confidence: 41%
“…The OCLN, ZO‐1, CLDN1, CLDN3, and CLDN4 are the main tight‐junction proteins in the mammary gland . In the current study, mammary expression of these proteins, except OCLN, showed no difference in the cows fed two diets.…”
Section: Resultscontrasting
confidence: 39%
See 2 more Smart Citations
“…There was a substantial increase in expression of CAF markers ACTA2, FAP, and S100A4 RNA and α-SMA protein (Supplemental Figure 2, D and E; see complete unedited blots in the supplemental material). Two characteristics of transformed fibroblasts in vitro are increased production of proinflammatory cytokines and increased migration (13,27). Conditioned medium from NE-treated cancer cells increased migratory potential (Supplemental Figure 2F) and expression of proinflammatory cytokines such as MCP1, CXCL1, MIF, GM-CSF, and G-CSF (Supplemental Figure 2G) in NOF151 cells.…”
Section: Resultsmentioning
confidence: 99%